"PERAN DATA GOVERNANCE DALAM MENINGKATKAN EFEKTIVITAS PENGAMBILAN KEPUTUSAN PERUSAHAAN DALAM BISNIS DI ERA DIGITAL" - Nova Azizah; Muhammad Irwan Padli Nasution (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to examine the role of data governance in enhancing the effectiveness of business decision-making in the digital era. Amid the rapid pace of digital transformation, companies are increasingly relying on data as the foundation for strategic decisions. However, without proper data governance, the quality of data becomes questionable, which affects the accuracy of decisions. This research employs a qualitative method through a library research approach, reviewing academic literature and previous studies related to data governance and decision-making management. The findings indicate that effective implementation of data governance can improve data quality, accuracy, and availability, thereby strengthening the foundation of the decision-making process. Moreover, companies that integrate data governance into their business strategies tend to be more adaptive, efficient, and competitive in facing digital challenges.